2006
DOI: 10.1017/s0317167100004698
|View full text |Cite
|
Sign up to set email alerts
|

Referrals for Movement Disorder Surgery: Under-Representation of Females and Reasons for Refusal

Abstract: Although deep brain stimulation (DBS) for movement disorders (MD) is an accepted option for selected patients who have failed maximal medical management, 1,2 only a small number are referred and only a proportion of those proceed to the operating room. Furthermore, a gender imbalance in operated patients was suggested previously. 3,4 Therefore, we sought to determine (i) if disproportionate numbers of males are referred compared to females, and (ii) why the patients referred for surgery failed to reach the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Earlier studies have shown that, in relation to the gender prevalence of PD, women are underrepresented among those treated with DBS [12, 14, 15, 31]. The reason for this is unknown but it has been suggested that women might be more “afraid” of (and hesitant towards) neurosurgery compared to men [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that, in relation to the gender prevalence of PD, women are underrepresented among those treated with DBS [12, 14, 15, 31]. The reason for this is unknown but it has been suggested that women might be more “afraid” of (and hesitant towards) neurosurgery compared to men [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, non-operated upon patients' own thoughts, considerations, and apprehensions concerning advanced therapy for PD have received scarce attention in the literature [10, 11]. This issue is all the more interesting in light of existing gender differences, with more men than women undergoing DBS for PD [1215] and given the current trend of suggesting DBS earlier in the disease progress [1618]. …”
Section: Introductionmentioning
confidence: 99%
“…Early estimations range from 1.6% to 4.5% (Morgante et al 2007), but have been criticized to underrate the ratio of eligible PD patients (Cacciola 2008). Several factors contribute to this underrating: Referring clinicians may underestimate the number of suitable patients (Oyama et al 2012), women are under-represented in those referred (Setiawan et al 2006), and the amount of suitable candidates could increase, if patients would be referred earlier to DBS (Charles et al 2012;Schüpbach et al 2013). Therefore, a more reasonable guess is that 10-20 % of PD patients may qualify for DBS (Christen and Müller 2012).…”
Section: Infrastructure Dimensionmentioning
confidence: 99%
“…Cognitive impairment has been reported as the most frequent cause of exclusion for STN DBS surgery [26,29,34,64,68,69]. This strict criterion has been supported by cognitive changes observed after STN DBS in elderly patients without cognitive impairment before surgery [70] and further cognitive worsening in patients with pre-existing impairment [71,72].…”
Section: Neuropsychologymentioning
confidence: 92%